TEACHING OF SOCIETY IN THE FUNCTION OF DEVELOPING ENVIRONMENTAL AWARENESS OF FOURTH GRADE PRIMARY SCHOOL PUPILS (Heritage, 2022)
In this paper, we dealt with the environmental awareness of fourth-grade elementary school pupils from the area of ​​Kosovo and Metohija on a sample of 170 pupils. The obtained data confirm the general research hypothesis and all specific hypotheses. Through the analysis of specific research hypotheses, it was found that children understand the importance of a clean environment, they like to spend time in nature, they are engaged in environmental protection, they are interested in learning about it at school, as well as through the Science course.The implications arising from the conducted research are reflected in the fact that children of younger school age from the area of ​​Kosovo and Metohija have a highly developed environmental awareness. The obtained data open up space for further examination of the environmental awareness of pupils in lower grades, as well as examination of the factors that contribute to the development of environmental awareness.
Keywords: environmental awareness, fourth-grade elementary school pupils, environment, science teaching